KOMUNIKASI BISNIS YANG ETIS: Sebuah Tinjauan Kritis - Ngorang Philipus (Jurnal Komunikasi dan Bisnis, 2018)
Every business action needs business comunication for getting profits. For getting profit, variously business communication strategics and technics are used to get it. Practically business comunication tends to manipulate even to lie the business stakeholder. Ethically this way is morally evil. Business communication ethics discourse needs to minimize these tendencies. In this term, business communication ethics should be understood as moral rules. These moral rules manage the business actor’s behavior in business activities. It has been formed ini deontology, utilitarian, justice, rights and virtuosity ethics. Business communication ethics critically review the business communication practice. In the moral philosophy perspective, profit oriented business communication produce domination stucture in the form of monologal business communication. Business communication ethics will produce the ethical business communication by deconstructing domination structure of monologal business communication. It will formed by esthablising the new rules and strengthening the civil society. It means that business communication ethics clarifies that ethical business communication deals not only with moral rules but also with social structure that support and hamper the ethical communication business practices. It is in dialogal business communication actions or practices.Keywords: business communication, ethics, domination structure, dialogal communication